Adsorptive Removal and Recovery of Aluminium (III), Iron (II), and Chromium (VI) onto a Low Cost Functionalized Phragmities Karka Waste - Regmi, Shukraraj; Ghimire, Kedar Nath; Pokhrel, Megh Raj; Khadka, Deba Bahadur (Journal of Institute of Science and Technology, 2015)
Chemically modified adsorbent based on Phragmities stem has been investigated by treating with concentrated sulfuric acid at 2:1 weight/volume ratio. The maximum loading capacity for Al(III) and Fe(II) onto phosphorylated charred Phragmities waste PCPW adsorbent was found to be 148 mg/g and 200 mg/g, while for Cr(VI) 200 mg/g, respectively, at their optimal pH. Similarly, it was 166.66 mg/g and 90.90mg/g for Al(III) and Fe(II) onto the charred Phragmities waste CPW, respectively. The adsorption process followed the Freundlich isotherm and pseudo-second order kinetic models. The desorption of the loaded metal ions recovery was found to be to the extent of 82%, 91% and 100% for Al(III), Fe(II) and Cr(VI), respectively. Journal of Institute of Science and Technology, 2015, 20(2): 145-152